(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service program enhanced farmers’ knowledge and skills in shallot (Allium cepa var. ascalonicum) cultivation in North Seram, Central Maluku District, through participatory extension services and modern agricultural technology transfer. The program involved 45 farmers over four months and employed a structured approach including preparation, socialization, hands-on field training, and post-training support. Faculty members from Pattimura University’s Plant Breeding Program facilitated three main technical sessions covering seed and seedling technology, cultivation practices, and breeding concepts, with active student participation as facilitators. Modern technologies introduced included tissue culture for quality seed production, drip irrigation systems, plastic mulching, GPS-based fertilization mapping, and integrated pest management using organic pesticides. The participatory methodology emphasized farmer engagement through presentations, demonstrations, group discussions, and peer-to-peer learning to ensure effective knowledge transfer and sustainable implementation. Results demonstrated significant program success: overall knowledge improvement of 60.2% (exceeding the 80% target in individual technical areas), technology adoption rate of 66.4% three months post-training, and preliminary productivity increases of 28.5% among participating farmers. Organic pest management showed highest adoption (82.2%), followed by improved seed selection (75.6%). Participant satisfaction reached 93.3%, with farmers forming sustainable discussion groups for continued knowledge sharing. This community-based extension program validates the effectiveness of participatory university-community partnerships for agricultural technology transfer, demonstrating potential for replication across Indonesia’s eastern provinces to improve farmer welfare and local economic conditions through enhanced shallot production quality and productivity.